2023
DOI: 10.25259/gjmpbu_153_2022
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Antimicrobial Resistance: An Emerging Silent Pandemic

Abstract: Before the outbreak of Coronavirus disease-19, one of the top 10 most risks identified by the World Health Organization (WHO) is antimicrobial resistance (AMR) that is also known as “silent pandemic.” According to Lord Jim O’Neill’s report, if no action is taken, then AMR will result in 10 million deaths annually by 2050. In the agricultural and medical sectors, the indiscriminate utilization of antimicrobial agents is getting worse. For the treatment of carbapenem-resistant Gram-negative infections, new antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…Furthermore, CZA susceptibility testing results were compared between CRE and CSE and it was found that CZA is susceptible in 42% of CRE isolates and 70% of CSE isolates. Similar results were reported by Ketan et al's study [9], in which about 30.6% of MDROs were susceptible to CZA, whereas the CZA susceptibility among CRO and CSO was 21.6% and 92.7%, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, CZA susceptibility testing results were compared between CRE and CSE and it was found that CZA is susceptible in 42% of CRE isolates and 70% of CSE isolates. Similar results were reported by Ketan et al's study [9], in which about 30.6% of MDROs were susceptible to CZA, whereas the CZA susceptibility among CRO and CSO was 21.6% and 92.7%, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…It is also noteworthy that there has been an increase in the rates of "difficult to treat" BSIs due to MDROs globally, which are resistant to carbapenem as well as various other β-lactam groups of antimicrobials, leaving very limited therapeutic options. Given this problem, it is very crucial to be aware of the susceptibility patterns of newly available agents and their efficacy in treating MDR infections [7][8][9][10]. Hence, in the present study, we evaluated the efficacy of the most commonly used method, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These negative impacts are worsened by the emergence of multidrug-resistant (MDR) pathogens [10] [19] [20] [21] [22]. Due to these global consequences, AMR is now termed a pandemic [23]- [32] and is among the top 10 threats to global public health [33] [34] [35].…”
Section: Introductionmentioning
confidence: 99%
“…AMR arises from the evolution of bacteria, viruses, fungi, and parasites, which cease to respond to antimicrobial agents. The misuse and excessive intake of antibiotics, along with the lack of information about AMR, contribute to the development of this threat [ 1 , 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%